Study of hystological characteristics of uterus and oviducts of Nelore cows and heifers (Bos primigenius indicus) - Monteiro, Cristina Maria Rodrigues; Farias, Eduardo Cunha; Perri, Silvia Helena Venturoli; Souza, Wilson Machado de (Brazilian Journal of Veterinary Research and Animal Science, 2003)
In this research were investigated comparative histological aspects of uterine horns and oviducts in Nelore cows and heifers. Thirty samples of each group were used, wich were fixed in 10% tamponed formol processed and embedded in paraffin. The histological sections of 6 mm were stained with hematoxilin and eosin, Mallory's trichrome ( to evidence colagens fibres), Weigert (to evidence elastic fibres) and Silver salts (to evidence reticular fibres). The results showed that exist differences in the histology of the uterine wall among cows and heifers, more evident in cows. The frequency of histological variations is higher for two uterine horns in cows. There is no significative difference among histological variations in the right and left horns. The characteristic variations are presents in the endometrium and miometrium, being the last one more conspicous. There are no differences of histological variations among cows and heifers and among the right and left oviducts and they do not present any relation to the uterine variations.